Difficulties in Conducting Scientific Research Faced by University Students (A Field Study on a Sample of Students of the Faculty of Social and Human Sciences at the University of Saida) - Merahi , Abdelkrim; Mehadji, Ben Maachou (Indonesian Journal of Social Science Research, 2025)
This study aimed to identify the challenges faced by university students in conducting scientific research and to examine whether these challenges differ based on gender or academic level. The study was conducted with a sample of 90 students from the Faculty of Social and Human Sciences at Saïda University. A descriptive approach was used to analyze the data. The results revealed that university students experience significant difficulties in conducting research. These challenges were ranked in the following order: first, difficulties related to research management, followed by issues related to academic preparation, difficulties related to the supervisor, and finally, difficulties related to the student researcher. The study also found no statistically significant differences in the difficulties of conducting scientific research based on gender. However, there were statistically significant differences related to the academic level of the students.